Understanding and Incorporating God Representations Within Counseling. Issue 2 (7th October 2019) - Bayne, Hannah Barnhill; Tylsova, Marie
Abstract : The religious and spiritual identity of a client may be relevant to the counseling process, and thus counselors should be prepared to integrate these components within treatment. The authors consider the assessment and exploration of God representations (i.e., God images and concepts) to understand and integrate religious and spiritual meanings within the context of a client's presenting concerns. The authors provide examples, strategies, and considerations for how to apply God representations within counseling.